Mimetic mechanicity: the Iron Foundry and vernacular internationalism in the 1930s - Masters, G (Cambridge University Press, 2023)
In the 1930s, the Iron Foundry, a short orchestral piece by the Soviet composer Aleksandr Mosolov, became hugely popular with audiences across Europe, North America, and beyond. Reassembling the fragmented archives of its performance and reception histories, this article sets out to follow the work on the circuitous routes that ensued. Addressing issues including programmaticism, the reception of Soviet music, and the history of comedy, I show how Mosolov's composition became a lightning rod for larger debates about concert music's relationships with modernity, politics, and mass entertainment. The case of the Iron Foundry, I suggest, illustrates how the pleasures of machine aesthetics – and, more specifically, a stylized idiom of mechanized gesture distinctive to the period – became widely assimilated into what we might call the vernacular internationalism of the interwar middle classes.